2018
DOI: 10.1002/hpja.41
|View full text |Cite
|
Sign up to set email alerts
|

Adopting healthier cooking oils: Findings from a qualitative study among independent food outlets in a rural district in Australia

Abstract: Issue addressed This study explored key factors that motivated independent food outlets to voluntarily adopt healthier cooking oils following a health promotion intervention. Methods Sixteen food outlet managers from the Cessnock Local Government Area (LGA) participated in semi‐structured interviews and a brief questionnaire which explored factors determining what cooking oils they use in preparing deep‐fried foods. Interviews were analysed thematically and closed responses to survey questions using descriptiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The Socio-Economic Status and Activity in Women in Australia study identified that women from higher SES were less likely to consume fast food and were more likely to consume meals from non-fast-food restaurants than women from lower SES groups [ 35 ]. Government policies may also enable better choices when eating out such as legislation regarding the reformulation of foods to reduce fat, salt and sugar content [ 36 ] and the food industry use of healthier cooking practices such as the replacement of oils high in saturated fat with healthy oils [ 37 , 38 ]. Policies and new practices could reduce the promotion of discretionary foods [ 39 ], the use of pricing to support smaller serving sizes of discretionary items and substitution of lower energy side dishes such as salads to replace chips [ 40 ] could also be used.…”
Section: Discussionmentioning
confidence: 99%
“…The Socio-Economic Status and Activity in Women in Australia study identified that women from higher SES were less likely to consume fast food and were more likely to consume meals from non-fast-food restaurants than women from lower SES groups [ 35 ]. Government policies may also enable better choices when eating out such as legislation regarding the reformulation of foods to reduce fat, salt and sugar content [ 36 ] and the food industry use of healthier cooking practices such as the replacement of oils high in saturated fat with healthy oils [ 37 , 38 ]. Policies and new practices could reduce the promotion of discretionary foods [ 39 ], the use of pricing to support smaller serving sizes of discretionary items and substitution of lower energy side dishes such as salads to replace chips [ 40 ] could also be used.…”
Section: Discussionmentioning
confidence: 99%